A novel mutation in ZP3 causes human ovulatory dysfunction and oocyte maturation arrest - Yingxue Liu; Guanghui Yuan; Yameng Hui; Xiaoxiao Wang; Jiashan Li; Jiao Zhuang; Huaiqian Dou; Linfang Han; Duan Li; Cuifang Hao (Journal of Ovarian Research)
Abstract Background Ovulatory dysfunction and oocyte maturation arrest are among the common causes of female infertility, but the genetic etiology of these phenotypes is not well understood. The ZP3 gene is responsible for coding the oocyte zona pellucida (ZP), and ZP3 mutation clinically manifests as abnormal zona pellucida or empty follicle syndrome. Nevertheless, its role in the process of ovulation and maturation of oocytes has rarely been reported. Case presentation In our study, we performed whole-exome sequencing in a 26-year-old proband with ovulatory dysfunction and oocyte maturation arrest, and we identified a novel heterozygous mutation in ZP3 (NM_001110354.1: c. 662 C > T, p.Pro221Leu), which is located within the ZP domain. The effects of the mutation were investigated through in vitro studies in HeLa cells, which revealed that the mutation resulted in a significant decrease in ZP3 protein levels. Additionally, the maturity of oocytes obtained from the patient with ZP3 mutation was significantly improved through the dual trigger treatment protocol, and the proband ultimately had a successful live birth. Conclusions Our findings expanded the pathogenetic spectrum of the ZP3 gene, which provided insights for treating patients with ovulatory dysfunction and oocyte maturation arrest related to ZP3 mutations. Clinical trial number Not applicable.